풍하중에 의한 바지선의 예인 시 거동특성 변화에 관한 연구 - 남보우(Bo Woo Nam); 최영명(Young-Myoung Choi); 홍사영(Sa Young Hong) (Han-guk haeyang gonghak hoeji (Online), 2015)
This paper presents the results of a numerical study on the towing characteristics of a barge under various wind conditions. First, stability criteria, including the wind force, were derived based on the linear motion equations of a towed vessel. The effect of the wind force on the towing stability was investigated using stability criteria. Next, towing simulations were carried out using a nonlinear time-domain simulation method. In this case, the towline was modeled as a simple spring-damper, and the wind force was computed using the wind coefficient from CFD calculations. Simulations were conducted for a barge under a constant towing speed and constant wind speed conditions. The effect of the wind direction on the slewing motion was also observed. In addition, a series of numerical simulations using variable wind speeds were performed for the present barge with and without a skeg.